Effect of Extraction Time on Chemical, Physical and Organoleptic Characteristics of South Asian Applesnail (Pila ampullacea) Protein Concentrate - Hasanah, Nurul; Nasyiruddin, Riya Liuhartana; Utpalasari, Rih Laksmi; Ilunanwati, Elok; Navicha, Willard Burton (CV Media Inti Teknologi, 2024)
This research aims to investigate the effect of protein extraction time using 90% ethanol on the protein concentrate product's physical, chemical, and organoleptic characteristics. The findings of this study could promote the use of protein concentrate developed from SAA. The study was conducted from April to June 2024, utilizing SAA collected from rice fields in the PALI (Penukal Abab Lematang Ilir) Regency, South Sumatra Province, Indonesia. A completely randomized design was employed, using different extraction times of proteins from SAA with 90% ethanol. Four extraction time levels were tested: 0 hours (P0 or control), 24 hours (P1), 28 hours (P2), and 32 hours (P3), each with three repetitions. Data were analyzed using ANOVA, followed by a post-hoc test employing Duncan's multiple range test, utilizing SPSS version 20.0. Results have shown that the optimal protein extraction time was P2 (28 hours), yielding a protein concentration of 51.6% on a dry basis. Additionally, protein profile analysis conducted via SDS-PAGE revealed the presence of histone proteins and an antibacterial protein derived from snail mucus in SAA. Treatment P2 exhibited five distinct protein bands with molecular weights of 17 kDa, 20 kDa, 25 kDa, 35 kDa, and over 48 kDa respectively. On the other hand, treatments P1 and P3 displayed only three protein bands that are 20 kDa, 35 kDa, and over 48 kDa. Results from the organoleptic analysis indicated that protein isolates with suitable attributes in terms of color and aroma were obtained from treatment P1 (24-hour extraction). This study has potential applications in the food industry.